Factors influencing age at diagnosis of primary ciliary dyskinesia in European children - Kuehni, Claudia Elisabeth; Frischer, Thomas H.; Strippoli, Marie Pierre Francoise; Maurer, Elisabeth; Bush, Andrew J.; Nielsen, Kim Gjerum Jerum; Escribano, Amparo Fernandez; Lucase, J. S A; Yiallouros, Panayiotis K.; Omran, Heymut; Eber, Ernst; O'Callaghan, Christopher Liam; et al. (My University, 2010)
Primary ciliary dyskinesia (PCD) is a hereditary disorder of mucociliary clearance causing chronic upper and lower airways disease. We determined the number of patients with diagnosed PCD across Europe, described age at diagnosis and determined risk factors for late diagnosis. Centres treating children with PCD in Europe answered questionnaires and provided anonymous patient lists. In total, 223 centres from 26 countries reported 1,009 patients aged <20 yrs. Reported cases per million children (for 5-14 yr olds) were highest in Cyprus (111), Switzerland (47) and Denmark (46). Overall, 57% were males and 48% had situs inversus. Median age at diagnosis was 5.3 yrs, lower in children with situs inversus (3.5 versus 5.8 yrs; p<0.001) and in children treated in large centres (4.1 versus 4.8 yrs; p=0.002). Adjusted age at diagnosis was 5.0 yrs in Western Europe, 4.8 yrs in the British Isles, 5.5 yrs in Northern Europe, 6.8 yrs in Eastern Europe and 6.5 yrs in Southern Europe (p<0.001). This strongly correlated with general government expenditures on health (p<0.001). This European survey suggests that PCD in children is under-diagnosed and diagnosed late, particularly in countries with low health expenditures. Prospective studies should assess the impact this delay might have on patient prognosis and on health economic costs across Europe.
Keywords: Bronchiectasis; Ciliary motility disorders; Diagnosis; Epidemiology; Kartagener syndrome; Primary ciliary dyskinesia